Dissolved cadmium in the Southern Ocean: Distribution, speciation, and relation to phosphate - Baars, Oliver; Abouchami, Wafa; Galer, Stephen J. G.; Boye, Marie; Croot, Peter L. (Limnology and Oceanography, 2014)
We report isotope dilution analyses of dissolved cadmium (Cd) and electrochemical Cd speciation measurements in the Atlantic sector of the Southern Ocean. Bioavailable inorganic Cd is. 100 times higher in near-surface waters south of the Polar Front compared to the Subantarctic Zone because of upwelling and reduced complexation by organic Cd ligands. To trace local changes in the relation between Cd and P, we examine the deviations from a linear deep-water Cd vs. P relation (Cd*), and find that changes in Cd* coincide with the position of frontal systems and covary with primary productivity and total dissolved Mn and Fe concentrations. These covariations agree with potential local changes in phytoplankton Cd uptake rates, resulting from differences in the availability of Cd, Zn, Mn, and Fe. A band of negative Cd* values is associated with formation of Subantarctic Mode Water (SAMW) and Antarctic Intermediate Water (AAIW). In contrast to SAMW, which may export low Cd : P ratios from the Southern Ocean, the Cd : P ratios in AAIW increase by mixing with underlying Upper Circumpolar Deep Water before being exported from the Southern Ocean. Deep waters show constant Cd : P ratios, and both elements behave conservatively with end-member mixing between deep waters of the Weddell Gyre, the Antarctic Circumpolar Current, and inflowing North Atlantic Deep Water. Overall, our results support the hypothesis that the kink in the global Cd vs. P relation is largely caused by high Cd : P uptake ratios in the trace-nutrient-limited Southern Ocean.